Impartiality within political reporting and election coverage - Richard Thomas (The Routledge Handbook of Political Campaigning, 2024)
Impartiality is key within election reporting, since in principle, it ensures that all political sides are represented, and audiences are given multiple perspectives. This, it is reasonable to conclude, means that all parties are given the same opportunities to promote their electoral messages. But within an increasingly fragmented global media landscape, the policing of impartiality is changing, and its value is often contested by those who must adhere to it. This chapter considers impartiality from historic and regulatory perspectives and identifies ways in which it is difficult to practice, and how it can be breached. Despite growing claims that impartiality should be reduced or diminished, the chapter concludes that this normative tenet of journalism should be protected, and that any changes to it should be made with caution.